Spatial modelling improves genomic evaluation in Tanzanian smallholder admixed dairy cattle - Houaga, I.; Mrode, Raphael A.; Ojango, Julie M.K.; Ekine-Dzivenu, Chinyere C.; Okeyo Mwai, Ally; Nziku, Z.; Nguluma, A.; Lavrenčič, E.; Lindgren, F.; Pocrnic, I.; Djikeng, Appolinaire; Gorjanc, G. (BioMed Central, 2026)
Background: Smallholder dairy production systems in low-and middle-income countries are characterised by large phenotypic variance due to diverse environmental effects, farming practices, and crossbreeding. Furthermore, small herds, low genetic connectedness, and limited data recording challenge accurate separation of environmental and genetic effect in such settings, limiting genetic improvement. Here, we evaluated the impact of modelling spatial variation between herds to address these challenges and improve the accuracy of genomic evaluation for Tanzanian smallholder dairy cattle.